Media, Religion, and the Public Sphere - Mihai, Coman (Religions, 2023)
In the present study, I undertake to show that the public sphere can be constructed within the frames of a discourse loaded with religious symbols, either as part of religious institutions and manifestations, or, in a more interesting case, through the media discourse. I want to show that media functions as a ritualizing agent, which builds symbolic spaces of action and thinking. Journalists accomplish this by presenting events as if they had pre-established and immutable order and meaning, set within a religious system. The ritualization of the journalistic performance and the mythologization of the representation of events are some of the strongest tools for promoting a representation of events in a language loaded with religious symbols and to outline a public sphere constructed in a religious frame. Thus, using a sacralizing language, media creates a religious public sphere, which function as a liminal, subjunctive framework: it is possible to assume that now a new type of public sphere, defined by a religious frame, is developed, in a social context and symbolical frame that are totally different to the usual circumstances of a religious experience.